الجريدة الرسمية العدد 39 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 2440 لسنة 2024 -- قرار رقم 2441 لسنة 2024 -- قرار رقم 2442 لسنة 2024 -- قرار رقم 2443 لسنة 2024 -- قرار رقم 2444 لسنة 2024 -- قرار رقم 2445 لسنة 2024 -- قرار رقم 2706 لسنة 2024